A Description of Olusuba Morphophonology: Towards Preservation of an Endangered Language - Sande, Walter Ochieng (JOOUST, 2019)
Language plays an important role in cultural preservation, linguistic diversity, cultural identity, accumulated wisdom and some knowledge embedded in it. A language is in danger when it is on the brink of losing these five values. The five values are lost when speakers of the endangered language cease to use it or use it in an increasingly reduced number communicative domain and stop to pass the language from one generation to the next. Olusuba is faced with a similar situation. It is thus classified as an endangered language. Sociolinguistic surveys have been undertaken to evaluate vitality of the endangered Olusuba and establish factors responsible for the language’s endangerment. These surveys have been done with an aim of revitalising Olusuba but the language still faces an onslaught of dominant others like Dholuo. Structurally, language consists of linguistic universals phonetics, phonology, morphology, syntax, semantics and pragmatics. Once a language dies out, these linguistic universals become extinct in that particular language yet they are relevant in informing conclusions about universal properties of the languages in the world. Description of linguistic universals of an endangered language has been proposed as an alternative measure towards preservation of the language. This study, therefore, endeavored to describe the phonology and morphology (morphophonology) of Olusuba, given that phonology and morphology are considered prerequisites for the description and analysis of any language’s grammar. To achieve this, the research was guided by three objectives. First, was to discuss the phonological patterns of Olusuba. Second, was to describe the morphological patterns of Olusuba. Third, was to examine the morphophonemic patterns of Olusuba. To meet the three objectives, the study employed a descriptive analytic research design. The target population for this research was native speakers of Olusuba. The study used snowball sampling technique to identify subjects from the target population. From the accessible population, the researcher purposively sampled 3 informants who were used in generating and verifying data. Data in this study was collected through elicitation, audio recording and note taking, using the Swadesh list, an elicitation frame, an audio recorder, a notebook and a pen. Audio recorded data was played back and cross-checked using notes for analysis. Preliminary data analysis involved categorisation of words into word classes. This was then followed by a description of the phonological and morphological patterns of the words. The patterns described were then analysed in the Optimality Theory framework. From the analyses of the collected data, it is established that synchronically Olusuba has 15 noun classes determined by the prefixes that nouns take and the resultant meaning. It is also established that Olusuba has an agreement system dependent on the noun class prefixes. In terms of syllable structure, Olusuba is characterised by nine syllable structures four of which are bimoraic. Long vowels have two sources in this language: underlying and derived. Olusuba was also found to exhibit Nasal-Consonant sequences as clusters. Verbs in Olusuba were found to be hierarchical in which case the inflectional and derivational morphemes that define hierarchies occupy specific slots within verbal templates. Six morphophonemic processes namely glide formation, vowel assimilation, vowel harmony, post- nasal fortition, nasal deletion and nasal place assimilation, were realised to take place in Olusuba purposely to ease articulation of Olusuba words. Documentation of the findings of this study is expected to provide archival preservation of the endangered Olusuba. The preserved findings are intended to help in revitalisation of Olusuba.